Preliminary studies: Analysis Of Student Needs For The Use Of Multiple Integral E-Module Of Mathematics Physics I Course - Diki Chen; Astalini; Dwi Agus Kurniawan (Buana Pendidikan, 2022)
The purpose of this research is to find out how the level and opinion regarding the multiplemultiple integral e-module material that is planned to be developed. This type of research is a mixed method with the sampling technique used is purposive sampling. The sample used is an active student of regular class B 2019 who has contracted a physics mathematics course I. The instruments used are in the form of questionnaires and interview sheets which are analyzed using descriptive statistics for questionnaires and interviews are analyzed using miles and huberman. The results obtained indicate that most of the samples think that the e-module is a very good idea, this can be seen from the results of descriptive statistics, the average value is 22.4 which is in the required category, the results of this quantitative data are strengthened by the results of interviews that mostly support the creation of this e-module.